The Role of HACCP Method in Determining Drinking Water Quality - Karnaningroem, N; Sunaya, M U L (IOP conference series. Earth and environmental science, 2020)
One of the main daily needs of human beings is drinking water. Clean drinking water can sustain every aspect of human life. From time to time, humankind already discovered multiple water resources which can be used in various ways. One of them is mineral bottled water. Yet not even this water source is guaranteed safe to be consumed. There might be many contaminants contained in the mineral bottled water production process. This triggers the need to form an applicable, comprehensive, and standardized method to determine which drinking water sources are safe for consumption. One of the methods which can fulfill the requirements is HACCP. HACCP (Hazard Analysis and Critical Control Point) is a system to analyze risks by determining a sufficient controlling and supervision method to avoid irregularity in the production system. There are five primary principles in HACCP method, i.e. analyzing the risks on the system, determining critical control points and critical limits, arranging monitoring procedure and organizing corrective action in the diversion of critical limit which surpassed toleration limit. Mineral bottled water production system can be an ideal subject for the application of HACCP method due to its detailed system which can be analyzed further.